Logical Fallacies in EFL Learners' Argumentative Writings - El Khoiri, Niamika; Widiati, Utami (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
Logical fallacies are common errors in reasoning that will undermine the logic of an argument. In argumentative writing, the presence of logical fallacies such fallacies shows either illegitimate arguments or irrelevant points, and are often identified because they lack evidence that supports their claim. The purpose of the study is to identify and discuss logical fallacies in the argumentative writing of Indonesian EFL learners. 40 argumentative essays were collected from the students of the English Department of the State University of Malang who have passed all the writing courses, including the course on argumentative writing. The results of the study shows that students still produced a number of logical fallacies in their work, some of which were so basic they can actually be avoided through simple, explicit instruction. Some pedagogical implications of the findings are also discussed.